Ingesting amino acid-carbohydrate prior to and during consecutive bouts of resistance training elevates resting energy expenditure - Hackney, K.; Kelleher, A. R.; Ploutz-Snyder, L. L. (The Journal of Strength and Conditioning Research, 2010)
Increases in resting energy expenditure (REE) and decreases in the respiratory exchange ratio (RER) have been reported following a single bout of resistance training (RT), indicating enhanced energy utilization and a greater reliance on lipids. It is hypothesized that elevations in REE occur because the synthesis of proteins following muscle damage is energetically expensive, requiring four adenosine-triphosphate equivalent molecules for every amino acid added to the peptide chain. During this process, there may be a greater reliance on lipids in order to meet the required energy need. Recently, a wealth of evidence suggests that timing the intake of amino acid-carbohydrate (AACHO) close to the RT session can increase muscle protein synthesis and reduce indicators of muscle damage. Thus, this strategy could modulate REE and RER following RT and have significant implications for body composition. To determine the effect of timed AACHO intake with consecutive days of RT on REE, RER, and rate of perceived muscle soreness (RPMS). Ten resistance-trained, male participants (23 +/- 0.8 yrs, 175 +/- 3 cm, 77.8 +/- 4 kg, 14 +/- 2%) completed two separate seven-day trials in a double-blind counterbalanced design. In trial 1, REE, RER, and RPMS were assessed each morning (~6:30am) with days 1 and 2 serving as baseline. After assessments on days 2, 3, 4, and 5, ~979 kJ of either AACHO (22.5g protein, [6g essential amino acids], 35g sugars) or carbohydrate only (CHO) (58.5g sugars) was consumed with RT (3 sets, 6 exercises, 75% 1 RM, lower body RT on days 2 and 4, upper body RT on days 3 and 5). Half of the supplement was provided immediately prior and the remaining amount was ingested during each RT session. Follow-up assessments of REE, RER, and RPMS also occurred on days 6 and 7 of the trial. Total energy intake was monitored during trial 1. In trial 2, all procedures were the same except the opposite supplement was provided. Nutritional intake during trial 1 was replicated in trial 2. There were no differences in total energy intake between or within AACHO (132 +/- 3.6 kJ[middle dot]kg-1[middle dot]day-1) or CHO (136 +/- 3.3 kJ[middle dot]kg-1[middle dot]day-1, p > 0.05). However, protein intake was greater in AACHO (1.72 +/- 0.06 g[middle dot]kg-1[middle dot]day-1) compared to CHO (1.49 +/- 0.04 g[middle dot]kg-1[middle dot]day-1, p < 0.05). A main effect of supplement condition was found for REE, indicating on average the elevation observed in AACHO (103 +/- 1.4 kJ[middle dot]kg-1[middle dot]day-1) was greater than CHO (99 +/- 0.81 kJ[middle dot]kg-1[middle dot]day-1, p < 0.05). Main effects for time were also determined for REE, RER, and RPMS ( Table 1). When AACHO was provided prior to and during RT, post-exercise REE was increased ~7% above that of CHO. Utilizing this simple strategy may increase energy utilization during the post-exercise period, which could facilitate reductions in body fat composition.